2019
DOI: 10.1016/j.ijscr.2019.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Delayed diaphragmatic hernia after open trauma with unusual content: Case report

Abstract: HighlightsThey are classic signs of progression in the presence of a hidden lesion in the diaphragm.The presence of the reported accessory spleen is only a possible variation.The use of thoracotomy is more indicated in cases with a later diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…Thoracic and abdominal access is commonly discussed in the current literature without a consensus about which technique is best. The actual agreement is that thoracotomy is indicated when the hernia presents late, meanwhile laparotomy is most appropriate immediately after trauma [11] . The main principles of hepatothorax repair due to traumatic diaphragmatic hernia include decompression, reducing the hernia back into the abdominal cavity, and ensuring secure closure of the diaphragmatic defect [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic and abdominal access is commonly discussed in the current literature without a consensus about which technique is best. The actual agreement is that thoracotomy is indicated when the hernia presents late, meanwhile laparotomy is most appropriate immediately after trauma [11] . The main principles of hepatothorax repair due to traumatic diaphragmatic hernia include decompression, reducing the hernia back into the abdominal cavity, and ensuring secure closure of the diaphragmatic defect [3] .…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, there were 4 delayed diagnoses which were confirmed 4 months to 12 years later after discharge from hospital. Delayed or missed diagnoses may place patients at risk for morbidity and mortality [ 27 29 ]. In some cases, it could be insidious for delayed hernia formation or small openings [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overall mortality was 27%. A recent case report by da Costa, et al 12 reported diagrammatic hernia with the displacement of abdominal viscera and two accessory spleens in a patient who had a history of stab trauma 9 years back. At the time of the injury, the trauma was managed with chest drainage without any evidence of abdominal injury.…”
Section: Discussionmentioning
confidence: 99%